Differential Difference Gain Amplifier (DDGA) and Its Applications - Satansup, Jetsdaporn; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2025)
This article introduces a CMOS circuit realization of the fully balanced differential difference gain amplifier (DDGA). The proposed DDGA is realized using four floating current sources operating under dual supply voltages of approximately ∓0.9 V. The proposed circuit can function as a differential difference gain amplifier with electronically adjustable gain both in voltage and current-modes. The application designs of the DDGA to implement a single-input three-output universal biquad filter and voltage-mode quadrature oscillator circuit are also suggested. PSPICE simulation results for the proposed DDGA and its applications are provided using 0.18-μm CMOS technology from TSMC.
Keywords: Differential Difference Gain Amplifier (DDGA); quadrature oscillator; transconductance amplifier; universal filter; voltage-mode circuits